The Effect of Addition of Lactobacillus plantarum S4512 on The Microbiological and Chemical Characteristics during Sorghum (Sorghum bicolor L. Moench) Fermentation - Tyas Utami; Rifa Nurhayati; Endang Sutriswati Rahayu (agriTECH, 2015)
The aim of this study was to investigate the population of selected bacteria and some chemical characteristics during sorghum fermentation with the addition of Lactobacillus plantarum S4512. Proteolytic L. plantarum S4512 isolated from natural sorghum fermentation was added into sorghum fermentation. Sorghum flour was mixed with sterile water (1:2 w/v) and then was inoculated with 1% v/v (about 109 CFU/ml) culture of L. plantarum S4512. Fermentation was carried out at 37°C for 24 hours. As a control, natural sorghum fermentation without addition of a starter culture was carried out at 30°C for 24 hours. During fermentation time, the amount of bacteria, acid producing bacteria, coliform and proteolytic bacteria were monitored. The titratable acidity, pH, soluble protein, and proteolytic activity were also measured. Addition of L. plantarum S4512 increased significantly the initial population of total bacteria, lactic acid bacteria and proteolytic bacteria to 107 CFU/ml and suppressed the growth of coliforms indicated by siginificantly decline of coliforms population after 6 h fermentation. The production of acid was doubled of that in the natural fermentation resulted in the lower pH to 3.14. Both natural sorghum fermentation and that with addition of proteolytic L. plantarum S4512 showed some proteolytic activities during fermentation.